The genus Tapiena Bolívar (Orthoptera: Tettigoniidae: Phaneropterinae; Holochlorini), with description of three new species from China - Liu, Chun-Xiang; Kang, Le (Zootaxa, 2010)
Tapiena Bolívar, 1906 (type species Tapeina acutangula Brunner von Wattenwyl, 1878) (Orthoptera: Tettigoniidae) is reviewed from China. A list and an identification key to ten species of Tapiena from China are given. Three new species are described: T. parapentagona sp. n., T. bilobata sp. n., and T. stridulous sp. n.. The previously unknown female of T. spinicaudata Liu & Xia, 1996 are described for the first time. Based on the examination of male stridulatory area, some known species are redescribed. Important and necessary illustrations, a distribution map, and discussion on distribution of Tapiena are provided.